Winning grants how to write winning grant proposals that will get you funding for your nonprofit - Ruell, James (James Ruell, 2022)
"Winning Grants is a comprehensive and approachable guide for anyone interested in grant work and in writing proposals to fund all types and sizes of library programs and projects, in all kinds of libraries, serving diverse communities"--